2012
DOI: 10.1521/bumc.2012.76.3.211
|View full text |Cite
|
Sign up to set email alerts
|

Narcissism: Its function in modulating self-conscious emotions

Abstract: This study focused on the functional aspects of narcissism in regulating self-conscious emotions (guilt, shame, hubristic pride, and achievement-oriented pride) as well as two other attribution styles (externalization and detachment). The authors investigated Japanese university students (N = 452) with regard to their self-conscious emotions using the Test of Self-Conscious Affect-3 (TOSCA-3) and their narcissistic personality using the short version of Narcissistic Personality Inventory (NPI-S). Structural eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…On the other hand, Japanese investigations using university age students as the research participants have confirmed that the TOSCA Shame Scale predicts maladjustment, but they have offered little or no support for the idea that the TOSCA Guilt Scale operationalizes adjustment (Hasui et al, 2009;Uji, Kitamura, & Nagata, 2011a,b;Uji, Nagata, & Kitamura, 2012). In short, the meaning of the TOSCA Shame and Guilt Scales across cultures clearly deserves additional research attention, especially in older samples.…”
mentioning
confidence: 99%
“…On the other hand, Japanese investigations using university age students as the research participants have confirmed that the TOSCA Shame Scale predicts maladjustment, but they have offered little or no support for the idea that the TOSCA Guilt Scale operationalizes adjustment (Hasui et al, 2009;Uji, Kitamura, & Nagata, 2011a,b;Uji, Nagata, & Kitamura, 2012). In short, the meaning of the TOSCA Shame and Guilt Scales across cultures clearly deserves additional research attention, especially in older samples.…”
mentioning
confidence: 99%
“…Narcissism involves a type of self-awareness whereby the self is more externalized and the individual is more likely to be materialistic (e.g., Rose, 2007; Uji, Nagata, & Kitamura, 2012). As Cisek, Hart, and Sedikides (2008) argue, “… for narcissists, money is the primary buffer against pain, meaninglessness, and other existential problems …” (p. 205).…”
mentioning
confidence: 99%
“…The implication, therefore, was that guilt may have negative mental health implications in Iran that are not evident in the West. This possibility seems apparent in at least some Japanese research as well (Hasui et al, 2009;Uji et al, 2011aUji et al, , 2011bUji et al, , 2012.…”
Section: Cultural Differencesmentioning
confidence: 92%
“…In exploring this possibility, Furukawa, Tangney, and Higashibara (2012) found that Korean, Japanese, and American children displayed differences in their average levels of shame and guilt, but linkages of these measures with other variables were similar across cultures. Japanese investigations examining university students also found that the TOSCA Shame Scale predicted maladjustment, but yielded little or no support for the contention that its guilt scale operationalized a more adaptive form of functioning (Hasui, Kitamura, Tamaki, Takahashi, Masuda, & Ozeki, 2009;Uji, Kitamura, & Nagata, 2011a, 2011bUji, Nagata, & Kitamura, 2012). In comparison to Western findings, therefore, studies in the Far East suggest that average levels of these moral affects may be different, that shame displays conceptually similar patterns of relationships with other measures, but that guilt may develop with less positive mental health implications.…”
mentioning
confidence: 95%